Spirituality and Hope in Old Age: Case Study of the Spiritual Academy - Stegu, Tadej (Verbum Vitae, 2025)
The article examines the meaning of spirituality and hope in old age, with a special focus on the Spiritual Academy, a programme at the Faculty of Theology of the University of Ljubljana. The research question focuses on how and why spirituality becomes an important factor in maintaining hope in old age and what role it plays in the context of a secularised society that often does not provide sufficient support for existential issues related to ageing. The article deals with both theoretical and empirical aspects of spirituality and hope in old age. It initially draws on relevant psychological, sociological and theological sources from established authors. The methodology of the following empirical section is based on the analysis of anonymous questionnaires completed by participants at the end of each year to investigate whether the programme meets the spiritual needs of older adults. For this purpose, a case study method with an evaluation questionnaire (with elements of a Likert scale and open questions) was used. The results show that the programme effectively addresses the need for spiritual and personal growth and provides a space for sharing experiences and reflection. Although the survey indicates a high level of participant satisfaction with the Spiritual Academy programme, it also points to areas for improvement, both in terms of organisation and content. The analysis revealed a strong interest among participants in topics related to spirituality and hope, confirming the importance of such non-formal educational programmes for older people.